TECHNICAL AND ECONOMICAL COMPARISON OF OVERFLOW DAM VARIANTS AT THE GRODNO WATER-POWER STATION - G. G. Krouglov; G. A. Korevitsky (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper considers various aspects pertaining to determination of main technical characteristics of water-development projects of water-power stations. Technical and economical characteristics of overflow dams at the Grodno water-power station are compared in the paper.The paper contains results of model investigations of two-tier overflow dam which is included in composition of the Grodno water-power station and presents methodology for calculation of pool integration behind two-tier dam which has been developed at the water-development and power engineering department. This methodology makes it possible to determine rate coefficient and compressed depth. In addition to this the paper gives technical and economical comparison of various designs of overflow dams at the Grodno water-power station, analyzes their cost and on the basis of this comparative analysis it is recommended to construct a two-pier dam.